2019
DOI: 10.1155/2019/5868935
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Oral Ang-(1-7) Restore Insulin Pathway and RAS Components Ameliorating Cardiometabolic Disturbances in Rats

Abstract: In prevention studies of metabolic syndrome (MetS), Ang-(1-7) has shown to improve the insulin signaling. We evaluated the HPβCD/Ang-(1-7) treatment on lipid metabolism, renin-angiotensin system (RAS) components, oxidative stress, and insulin pathway in the liver and gastrocnemius muscle and hepatic steatosis in rats with established MetS. After 7 weeks of high-fat (FAT) or control (CT) diets, rats were treated with cyclodextrin (HPβCD) or HPβCD/Ang-(1-7) in the last 6 weeks. FAT-HPβCD/empty rats showed increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Plasma levels of ANGT are reported to be modulated by hormones such as corticosteroid, oestrogen, thyroid hormones and angiotensin II [ 46 , 47 ], suggesting that hormone imbalance could influence RAAS and its dysregulation. The important role of RAAS in metabolic regulation is also explained by its two axes: ACE-2/Ang 1–7/Mas which has antiproliferative, antioxidant and anti-inflammatory functions with beneficial effects on hypertension, glucose intolerance and insulin resistance (IR); and the counter-regulatory ACE/Ang II/AT1 [ 48 ] with opposite effects. ACE-2 has been shown to play a protective role in lung disease through effects mediated by the Mas oncogene.…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of ANGT are reported to be modulated by hormones such as corticosteroid, oestrogen, thyroid hormones and angiotensin II [ 46 , 47 ], suggesting that hormone imbalance could influence RAAS and its dysregulation. The important role of RAAS in metabolic regulation is also explained by its two axes: ACE-2/Ang 1–7/Mas which has antiproliferative, antioxidant and anti-inflammatory functions with beneficial effects on hypertension, glucose intolerance and insulin resistance (IR); and the counter-regulatory ACE/Ang II/AT1 [ 48 ] with opposite effects. ACE-2 has been shown to play a protective role in lung disease through effects mediated by the Mas oncogene.…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
“…In the lung of IPF patients, ACE-2 is reported to be significantly depleted [ 49 ], suggesting that RAAS is important in the pathogenesis of IPF. In turn, the dysregulation of RAAS components can trigger many metabolic functions, such as those observed in metabolic syndrome and diabetes mellitus type 2 [ 48 ]. Indeed, in diabetic retinopathy, RAAS is an effector of vascular epithelial growth factor (VEGF) that drive the leakage of retinal blood vessels [ 50 ].…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
“…However, compared with aT1r, it is difficult to investigate the functions of AT2R, at least in part due to the relatively low expression levels in cells (23). Previous studies investigating ang ii and its receptors have primarily focused on the ang ii/aT1r axis (24)(25)(26)(27); therefore, the present study investigated the effects of BPa on hepatic damage and the ang ii/aT1r signaling pathway in a rat model of liver i/r injury. a previous study reported that 0.4 mg/kg/day BPa in rats is close to the current reference daily limit for human exposure by the u.S. environmental Protection agency (28).…”
Section: Discussionmentioning
confidence: 99%
“…In prevention studies, oral administration of Ang-(1–7) improved body mass, adiposity index, plasma triglycerides levels, glucose tolerance, insulin sensitivity in rats and mice fed with HF ( Oliveira Andrade et al, 2014 ; Williams et al, 2016 ) and fructose ( Giani et al, 2009 ; Muñoz et al, 2012 ) diets. Additionally, in recent studies ( Barbosa et al, 2019 ; Figueiredo et al, 2019 ) we have shown that oral treatment with Ang-(1–7) in rats, with established MetS induced by HF diet, was effective in restoring biometric, biochemical parameters, redox process, and RAS components in the liver and gastrocnemic muscle ( Figueiredo et al, 2019 ). Also, oral treatment with Ang-(1–7) was able to remodel the white and brown adipose tissue ( Barbosa et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These disorders are related to redox imbalance resulting in higher formation of reactive oxygen species such as superoxide and hydroxyl radicals, which can lead to mitochondrial dysfunction and accumulation of oxidized proteins and lipids ( Estadella et al, 2013 ; Peluso et al, 2017 ; Zacarias et al, 2017 ; Vona et al, 2019 ). In addition, HF diet induces liver damage related to various disorders occurring in the MetS such as IR, dyslipidemia, and increased adiposity ( Rosselli et al, 2014 ; Zacarias et al, 2017 ; Barbosa et al, 2019 ; Figueiredo et al, 2019 ). Additionally, in pancreatic b -cells, different concentrations of nitric oxide (NO) exerts positive or negative regulation of insulin secretion ( Meares et al, 2011 ) and thus improving or worsening the state of IR ( Kaneko and Ishikawa, 2013 ).…”
Section: Introductionmentioning
confidence: 99%